2015
DOI: 10.21273/hortsci.50.8.1213
|View full text |Cite
|
Sign up to set email alerts
|

Yield, Composition, and Antioxidant Capacity of Ground Cumin Seed Oil Fractions Obtained at Different Time Points during the Hydrodistillation

Abstract: Cumin (Cuminum cyminum L.) is an important essential oil (EO), medicinal, and spice plant from family Apiaceae. Cumin seed EO has wide applications in the food, liquor, pharmaceutical, and aromatherapy industries, and is extracted via steam or hydrodistillation of either whole or ground seed. The hypothesis of this study was that by capturing oil eluted at different timeframes during the hydrodistillation process (HDP), we could obtain oils of differential composition and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The extraction yield from P. capense seed (1.6%) is slightly similar to that obtained in the literature (1.98%) after 3 h of hydrodistillation from dried ground seeds (1.87%) (Bakarnga-Via et al, 2014). The differences in the extraction yields and those in the literature may be due to the place and period of harvesting of the plant, the variety of plant species used, the duration of extraction, the environmental variations (Zheljazkov et al, 2015).…”
Section: In Vivo Antibacterial Activitysupporting
confidence: 82%
“…The extraction yield from P. capense seed (1.6%) is slightly similar to that obtained in the literature (1.98%) after 3 h of hydrodistillation from dried ground seeds (1.87%) (Bakarnga-Via et al, 2014). The differences in the extraction yields and those in the literature may be due to the place and period of harvesting of the plant, the variety of plant species used, the duration of extraction, the environmental variations (Zheljazkov et al, 2015).…”
Section: In Vivo Antibacterial Activitysupporting
confidence: 82%
“…In previous studies, distillation time has been shown to alter the antioxidant capacity of the oil within a species, e.g . in cumin oil, in anise seed oil, in fennel seed oil, in Artemisia annua oil, male and female juniper, oregano, pine needle oil …”
Section: Discussionmentioning
confidence: 99%
“…Different methods are used for oilseed extraction including hydrodistillation, steam distillation, extraction with classical solvents, supercritical fluid extraction (SFE), headspace solvent micro extraction and solid phase microextraction (SPME) (Li et al, 2009). However, seed origins, maturity stages, environmental factors as well as extraction and analytical methods affect significantly the yield and the chemical composition of oils (Zheljazkov and Shiwakoti, 2015) (Table 1). radical scavenging, hydrogen peroxide scavenging and metal chelating activity (Table 3).…”
Section: Phenolics Flavonoids and Antioxidant Propertiesmentioning
confidence: 99%